DESCRIPTION OF CONCEPTUALIZATION AND TROUBLESHOOTING AFTER SEEING TUTORIAL VIDEO BRUSHING DENTAL WITH MODIFIED STILLMAN TECHNIQUES (Politeknik Kesehatan Kemenkes Bandung, 2020)
ABSTRACT Introduction: Conceptualization and problem solving involve the need to understand ideas and abstractions to make good judgments about one's oral health. This need is considered fulfilled if the client understands the reasons for recommended oral health care interventions such as participating in setting goals for dental health care and does not have questions about professional dental health care or dental care, and does not have questions about the cause of oral problems related to overall health, and the importance of suggested solutions to resolve the issue. Objective: Obtain an overview of conceptualization and problem solving after watching the video tutorial on brushing teeth with modified stillman techniques. Metode : This type of research is descriptive, which means the research conducted to make a picture or description of the situation objectively (Notoatmodjo, 2015). The situation that will be described in research on the Conceptualization and Problem Solving Overview After Seeing the Tooth Brushing Tutorial Video with Modified Stillman Techniques. Results: The results of the study obtained, the percentage of respondents who felt the video tutorial brushing their teeth with this Modified Stillman technique was 100% useful. This shows that the understanding of how to maintain the dental health of respondents is good. Conclusion: The majority of respondents stated that they would practice the tooth brushing technique with the modified stillman technique. Key Word : Conceptualization and problem solving, Video tutorials, Modified stillman 12Dental Nursing Department of Health Polytechnic Bandung.